2019
DOI: 10.1016/j.arth.2019.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intraoperative Periprosthetic Femoral Fractures During Primary Total Hip Arthroplasty. An Analysis From the National Joint Registry for England and Wales and the Isle of Man

Abstract: Risk factors for intraoperative periprosthetic femoral fractures during primary total hip arthroplasty. An analysis from the National Joint Registry for England, Wales and the Isle of Man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 17 publications
4
53
2
4
Order By: Relevance
“…Laaksonen et al [19] reported 10,113 primary UTHAs and demonstrated that the overall survivorship up to 8 years was 94.4-96.25%. However, a recent study showed no significant difference in survival between CTHA and UTHA [10]. This may partially be attributed to the low numbers (22 hip) in this study.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Laaksonen et al [19] reported 10,113 primary UTHAs and demonstrated that the overall survivorship up to 8 years was 94.4-96.25%. However, a recent study showed no significant difference in survival between CTHA and UTHA [10]. This may partially be attributed to the low numbers (22 hip) in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Data on long-term implant survival and HHSs remain lacking. Furthermore, limited literature has reported implant survival; however, most of these reports have been subject to the length of follow-up [10]. A previous study reported by Lazarinis showed approximately a revision rate of 7.5% after 10 years for CTHA [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study showed no significant difference in survival between CTHA and UTHA. 10 This may be partially attributed to the low number of hips (n = 22) in the study. 10 The 10-year survival rate after THA was recently reported in large-sample studies (>100 hips).…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, few reports have described implant survival, and most of these reports have been subject to a short duration of follow-up. 10 Lazarinis et al. 11 reported a 10-year revision rate of approximately 7.5% after CTHA.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars reported that the incidence of periprosthetic fractures after primary joint arthroplasty was 0.3% ~4.0%. Falling is an important risk factor and 75% of periprosthetic fractures are caused by falls [15,16].…”
mentioning
confidence: 99%